The effect of sorghum bagasse particles and composite density on the physical, mechanical and morphological properties of rigid polyurethane foam composites. Issue 1 (1st April 2022) - Aida, N; Munawar, S S; Argo, B D; Purnomo, D; Sutan, S M; Subiyanto, B; Ismadi,; Fatriasasi, W; Syahrir, A; Akbar, F; Kosasih, D P
Abstract: The sorghum bagasse (SB) particle was used as a filler for the manufacture of rigid polyurethane foam composites (RPUFC). The purpose of this research was to investigate the effect of SB particle content and variation of composite density on the physical, mechanical, and morphological properties of RPUFC. The RPUFC was created with five different volume fractions of SB particles (0, 2.5, 5, 7.5, and 10 wt.%) and three different composite densities (40, 50, and 60 kg/m 3 ). The SB particles, polyols, and isocyanate were mixed, poured, and formed in a closed mould. The physical and mechanical properties of the RPUFC were determined according to standard methods. The physical properties (moisture content, water absorption, thickness swelling) were increased with increasing SB particle content in the RPUFC. Meanwhile, the mechanical properties (flexural and compressive strengths) tended to decrease with increasing SB particles but increase with increasing density of RPUFC. The best RPUFC, which had properties equivalent to RPUFC without the addition of particles, was produced with the addition of 2.5% particles at densities of 50 and 60 kg/m 3 .